2013
DOI: 10.1021/jp404376t
|View full text |Cite
|
Sign up to set email alerts
|

Potential-Dependent Adsorption and Desorption of Perfluorosulfonated Ionomer on a Platinum Electrode Surface Probed by Electrochemical Quartz Crystal Microbalance and Atomic Force Microscopy

Abstract: Potential-dependent adsorption/desorption behavior of perfluorosulfonated ionomer (PFSI) on a platinum electrode was investigated by cyclic voltammetry, electrochemical quartz crystal microbalance (EQCM), and electrochemical atomic force microscope (EC-AFM) in a Nafion, that is, PFSI, dispersed aqueous solution without any other electrolyte. PFSI adsorbed on the platinum surface in the potential region between 0.1 and 0.8 V versus Ag/AgCl and desorbed from the surface at 1.1 V where place-exchanged Pt oxide wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
50
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(57 citation statements)
references
References 38 publications
5
50
2
Order By: Relevance
“…Figure 8 shows the Tafel plots for the ORR kinetic currents, which were obtained using Eq. 31,32 The Tafel slope is 65 mV · decade −1 for the bare Pt, which is close to a reported value above 0.82 V, 60 mV · decade −1 .…”
Section: Resultssupporting
confidence: 86%
“…Figure 8 shows the Tafel plots for the ORR kinetic currents, which were obtained using Eq. 31,32 The Tafel slope is 65 mV · decade −1 for the bare Pt, which is close to a reported value above 0.82 V, 60 mV · decade −1 .…”
Section: Resultssupporting
confidence: 86%
“…The absence of SA1's influence on either polycrystalline Pt or Pt/Vu (not shown) agrees with previous studies on adsorption of triflic acid (CF 3 SO 3 H) 41,42 and PFSA ionomer. 43 The authors reported a weak interaction, i.e. non-specific adsorption, between the sulfonate ion and Pt surface.…”
Section: Adsorption Impact Of Perfluorosulfonic Acids (Sa1 and Sa2)-mentioning
confidence: 99%
“…One possibility is the adsorption of sulfonic acid group in Nafion. [20][21][22] A mass-change measurement with an electrochemical quartz crystal microbalance using a Pt electrode in perfluorosulfonated ionomer solution demonstrated a mass increase during the anodic sweep. 20 Electrochemistry, 84 (7), 511-515 (2016)…”
Section: Oxide Formation/reduction Without Preceding Potential Holdmentioning
confidence: 99%